2016
DOI: 10.4137/cmwh.s34670
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prenatal Exercise on Offspring Health: A Review

Abstract: Research has continued to demonstrate that exercise during pregnancy is safe. Growing evidence supports that exercise during pregnancy is beneficial for mother and fetus during gestation, with benefits persisting for the child into adulthood. Regardless of income or socioeconomic status, exercise during pregnancy is associated with increased incidence of full-term delivery. Additionally, normalization of birth measures, such as birth weight, occurs when women perform regular exercise throughout gestation. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 91 publications
1
49
0
2
Order By: Relevance
“…Hence, there is good reason to assume that exercise during pregnancy is not harmful for the child’s neurodevelopment. Additionally, meta‐analyses and reviews addressing other short‐term outcomes report no harmful effects of exercise during pregnancy for mother, fetus or child, and conclude that exercise should be recommended …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is good reason to assume that exercise during pregnancy is not harmful for the child’s neurodevelopment. Additionally, meta‐analyses and reviews addressing other short‐term outcomes report no harmful effects of exercise during pregnancy for mother, fetus or child, and conclude that exercise should be recommended …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other observational studies have reported better orientation and behavioural regulation 5 days after birth, similar psychomotor and mental development at 1 year of age, higher IQ, vocabulary score and language development at 12–24 months of age, higher general intelligence and better oral language skills at 5 years of age, as well as better academic performance in school from 6 to 18 years of age among children whose mothers exercised during pregnancy. Three recent reviews conclude that physical activity may have positive effects on neurodevelopmental outcomes, and recommend RCTs investigating maternal exercise and neurodevelopment of offspring in a long‐term perspective …”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, regular PA can have various health benefits for mother and fetus, such as reduced symptoms of depression [ 2 ] and lower risks for excessive gestational weight gain [ 3 ], gestational diabetes mellitus [ 4 ], lower birth weight [ 5 ], preterm birth [ 3 ], and pre-eclampsia [ 6 ]. There is even evidence that PA during pregnancy may improve cardiac and neurobehavioral maturation of the offspring [ 7 ], which is in harmony with the premise of fetal programming [ 8 ]. Therefore, the American College of Obstetricians and Gynecologists [ 9 ] recommends that pregnant women, in the absence of medical or obstetric complications, participate in moderate-intensity activities for at least 20–30 min per day on most or all days of the week.…”
Section: Introductionmentioning
confidence: 99%
“…However it should be noted that in those cases, healthcare providers were obstetricians and not midwives due to their different healthcare model. Given the known health benefits for mother and baby when the mother is physically active (Moyer et al 2016), and the discordance found in the current study between published guidelines and midwives knowledge, it would seem prudent to ensure that appropriate access to training and CPD is readily available. However, only 4% of respondents reported having access to CPD in the area of PA guidance.…”
Section: Discussionmentioning
confidence: 84%